PENERAPAN REHABILITASI MEDIS DI RSKO TERHADAP PENGGUNA NARKOTIKA BERDASARKAN UNDANGUNDANG REPUBLIK INDONESIA NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Ishenna G Lalwani; Rugun Romaida Hutabarat (Fakultas Hukum Universitas Tarumanagara, 2021)
The application of the law is an application that has been determined by the government as a reflection of the rules that must be obeyed by law enforcement officials and the public. Indonesia's biggest case is a narcotics case where addicts and abusers get imprisonment. In fact, in Constitution Number 35 of 2009 about Narcotics, it has been regulated those narcotic addicts and abusers are required to get medical rehabilitation, but, punishment continues to occur. Medical rehabilitation is a treatment and care for curing addiction to narcotics addicts and abusers by providing guidance to addicts and narcotics abusers. In Decision Case Number 570 K/Pid.sus/2019 it is proven that the rehabilitation sanction is a very important sanction imposed for addicts and narcotics abusers as treatment of suspects. Legislation has explained that health efforts are highly indicated in the application of Law Constitution Number 35 of 2009 about Narcotics. The implementation of the law is not in line with the existing reality. A good law must be firm and clear in its application